2005
DOI: 10.12968/bjon.2005.14.7.17944
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the risk of MRSA infection: screening and isolating patients

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) continues to be a major cause for concern to health boards and trusts through the UK and the rest of the world. A review of literature sourced via Cinahl, Medline and Pubmed examines the discussions for and against screening patients for MRSA and isolating MRSA-positive patients as a means of managing MRSA within the hospital setting. The research evidence available on the ability of MRSA strains to spread within the healthcare setting and how this influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Importantly, restrictions are placed on the access and egress of patients, staff and visitors to limit the transmission of the infection. There is overwhelming evidence that supports the clinical and epidemiological use of these practices for source isolation and contact precautions in containing MRSA and other similar infections (Australian Government Department of Health and Ageing, 2004;Bissett, C N C N C N C N of source isolation, including loneliness, anger, neglect, abandonment, boredom and stigmatization (Knowles, 1993;Rees, Davies, Birchall, & Price, 2000;Ward, 2000). Gammon (1998) used a quasi-experimental research design and psychological tests to measure the stressful effects of hospitalisation and compared the results of patients isolated to those who were not.…”
Section: Ethicillin-resistant Staphylococcus Aureusmentioning
confidence: 99%
“…Importantly, restrictions are placed on the access and egress of patients, staff and visitors to limit the transmission of the infection. There is overwhelming evidence that supports the clinical and epidemiological use of these practices for source isolation and contact precautions in containing MRSA and other similar infections (Australian Government Department of Health and Ageing, 2004;Bissett, C N C N C N C N of source isolation, including loneliness, anger, neglect, abandonment, boredom and stigmatization (Knowles, 1993;Rees, Davies, Birchall, & Price, 2000;Ward, 2000). Gammon (1998) used a quasi-experimental research design and psychological tests to measure the stressful effects of hospitalisation and compared the results of patients isolated to those who were not.…”
Section: Ethicillin-resistant Staphylococcus Aureusmentioning
confidence: 99%
“…6,7,[9][10][11][12] Some researchers argue that targeted screening is not as effective as universal screening because a significant percentage of those identified by universal screening would not be identified by targeted screening 18,19 In england the Department of Health recommend universal screening for MRSA at admission. 20 In Scotland the health protection centre is currently undertaking a review of the clinical benefit and cost effectiveness of universal screening for MRSA in a whole health board.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Furthermore, many studies have identified the increased risk of developing MRSA infection in patients with MRSA colonisation. [6][7][8] The success of programmes to control MRSA centre around the fact that this previously unknown reservoir for MRSA is targeted, isolated and treated to prevent further spread and reduce risk of infection in the colonised individual. 6,9,10 There is also agreement that certain 'at risk' groups are more likely to be colonised with MRSA than others with many countries now recommending targeted admission screening.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As microorganisms causing nosocomial infections, Serriatia spp., Pseudomonas spp., Burkholderia spp., Staphylococcus spp., Legionella spp., Mycobacterium spp., Bacillus spp., Clostridium spp., MRSA, and VRE have often been discussed (Dubouix et al, 2005;.Cullen et al, 2005;Goenaga Sanchez et al, 2005;Trautmann et al, 2005;Moreira et al, 2005;Otaga et al, 2005;Allen and Griffith, 2005;Hsueh et al, 2005;Willems et al, 2005;Banning, 2005;Bissett, 2005;Exner et al, 2005;O'Neill and Humphreys, 2005;Duckro et al, 2005;Matsuki et al, 2005;Arrich et al, 2005;Ohangela et al, 2004;Pai et al, 2004;Conger et al, 2004;Kline et al, 2004;Wang et al, 2004;Tambyah et al, 2004;Axon et al, 2004;Shintani et al, 2004;Hernaiz et al, 2003;Moore et al, 2002;Barbeau et al, 1998;LaForce, 1997 speculated to be due to direct contamination via hands from health care employees to immunodeficient patients, but this has not been completely clarified yet. We have studied airborne and surface microorganisms in the dialysis room of Namiki clinic at Nagoya, Japan and confirmed that the origins of these microorganisms were mostly from people including doctors, nurses, and patients (Miki, 2003a, Shintani et al, 2004.…”
Section: Introductionmentioning
confidence: 99%